Correction: Persistence of symmetry-protected Dirac points at the surface of the topological crystalline insulator SnTe upon impurity doping. Issue 7 (25th January 2023) - Arroyo-Gascón, Olga; Baba, Yuriko; Cerdá, Jorge I.; de Abril, Oscar; Martínez-Casado, Ruth; Domínguez-Adame, Francisco; Chico, Leonor
Abstract : Correction for 'Persistence of symmetry-protected Dirac points at the surface of the topological crystalline insulator SnTe upon impurity doping' by Olga Arroyo-Gascón et al., Nanoscale, 2022, 14, 7151–7162, ; https://doi.org/10.1039/D1NR07120C .